Quebec's Anglohpone Communities and the Legacies of the Quebec Act, 1774-2024 - McGaughey, Jane G.V. (2025)
2024 marked the 250th anniversary of the Quebec Act, a landmark piece of legislation shepherded through the Westminster Parliament by then Governor of Quebec Guy Carleton, later known as Lord Dorchester. This paper explores the reactions of Anglophone communities in Quebec to Carleton’s actions in the 1770s and also in the 1980s, when the disappearance of “Dorchester Boulevard” in Montreal caused mixed reactions. Despite having been raised in an Irish Protestant family that benefited from the punitive anti-Catholic Penal Laws of the 18th century, Carleton broke with established British imperial policies of forced assimilation and territorial expulsion. Instead, he promoted a more pluralistic vision for Quebec where French Canadian Catholics enjoyed civil rights unheard of in the rest of the British Empire. However, while Carleton’s actions permanently affected future ideas of what defined “Canada,” they also alienated many members of the Anglophone community in Quebec City and Montreal on the eve of the American Revolution.

Remembering Drummondville’s First Families : A Very Special Heritage Tea and Talk - Centre for Access to Services in English (CASE) (2023)

They “Could Care for Our Elderly in Our Homes” : The Historical Impact of Black Caregivers - Williams, Dorothy W. (2023)
My aim is to interrogate prevalent assumptions about health and social services through a survey of notable chapters in the history of Black caregiving in Quebec. The assumptions have created expectations and a false narrative built upon historical myths and erasures that undergird the provincial population’s understanding of its relationship with Black caregivers. Blacks, both Francophone and Anglophone, though not exclusively so, have had significant connection to the care and well-being of Quebec’s residents. Black caregiving in Quebec is not recent—indeed, Black caregivers have been intimately tied to Quebec’s labour force aspirations and development for centuries. Even so, it is rarely acknowledged, to the point of being virtually unknown. This paper seeks to address those gaps in the narrative by presenting a timeline dating back to the 17th century. It will reveal intricate connections between the different periods when it comes to segregation, prejudice, migration, immigration quotas, and bans.
Parallel title: QUESCREN Working Paper no. 10

Sharing Our Stories - Neighbours Regional Association of Rouyn-Noranda (2023)

Stories of a Small “Shtetl” : Jewish History in Drummondville - Miller, Julie (2022)

Newsletter: August 2022 : Independence Special Edition : Volume 25.1 - Jamaica Association of Montreal (JAM) (2022)
Number of pages: 2

Money Raised for La Rose des Vents de Drummond and a Successful First Edition of the “History and Music” Concert Series - Centre for Access to Services in English (CASE) (2022)

Our Local Pioneers! : A Podcast on the Collaboration between Francophones and Anglophones in the Outaouais and their Contributions to Quebec Society, from Yesterday to Today - Nivischiuk, Jeanne (2022)

The Best-Treated Minority in the World : Historical and Discursive Analysis of a Cliché - Donovan, Patrick (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
Politicians, polemicists, and others have long referred to Quebec’s Englishspeaking community as the “best-treated minority in the world.”1 This loaded phrase has also been used to describe other minorities: French speakers within Canada as a whole, Indigenous peoples in Canada, and religious groups and minorities in many European and colonial contexts. Through a historical overview and discourse analysis, this paper traces how the phrase has been used and abused, justified, and criticized over time. The particular focus is the Quebec context. There, we see a shift from a largely consensual use of the phrase across all language groups to one that becomes increasingly divisive and problematic from the 1980s on. This shift parallels the English-speaking community’s evolving sense of itself as a minority in decline.
Parallel title: QUESCREN Working Paper no.5
Keywords: Official Language Minority Community (OLMC)

The Tourist Offer of the Whiteley Museum and its Surrounding Area on the Lower North Shore : A Quality Improvement Report - Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
This report analyzes the tourist offer in the eastern part of Quebec’s Lower North Shore, particularly the municipality of Bonne-Espérance, a region where English speakers make up the majority of the population. It focuses specifically on an institution in one of these municipalities, the Whiteley Museum. The report provides the authors’ suggestions to improve tourism development as a means to diversify the economy, potentially help reverse demographic decline, and build community vitality.

Resolution 2022-02 : Request to Maintain Race, Religion, and Culture as Central Themes in the Proposed Citizenship Course - Quebec Federation of Home and School Associations (QFHSA) (2022)

Allocation dans le cadre du Forum de QUESCREN sur l'éducation et la vitalité - Théberge, Raymond (2021)

Over 450 Years of Song: Religious Heritage Days Concert - Centre for Access to Services in English (CASE) (2021)

Resolution 2021-04 : Request to Revise and Improve the Secondary III and Secondary IV History of Quebec and Canada Curriculum - Quebec Federation of Home and School Associations (QFHSA) (2021)

Quebec Past and Present : 9th Colloquium on Quebec Studies / 9ème colloque sur les études québécoises - Eastern Townships Resource Centre (ETRC); Bishop's University; State University of New York Plattsburgh (2021)
issued: March 12, 2021/March 13, 2021

Society Pages - Morrin Centre (2021)
Number of pages: 32

Society Pages - Morrin Centre (2021)
Number of pages: 32

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 8

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (Southside Navigator, 2020)
Number of pages: 6

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (Southside Navigator, 2020)
Number of pages: 6

Black in Quebec : Systemic Racism in Our History - Davids, John; Fang, Xiaoyan; Galutira, Aileen (2020)

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (Southside Navigator, 2020)
Number of pages: 6

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (Southside Navigator, 2020)
Number of pages: 6

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (2020)
Number of pages: 6

Quebec Past and Present 2020 : Colloquium on Quebec Studies - Eastern Townships Resource Centre (ETRC); Bishop's University; State University of New York Plattsburgh (2020)
issued: April 3, 2020/April 4, 2020

A Posthumous Honour for a Conspicuous Life : Dr. Gaspard in Quebec - Williams, Dorothy (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
This story is an attempt to understand an unknown individual whose life was significant but has now been forgotten. He was American-born, yet his mother tongue was French. He served Canada in French units but embraced the English-speaking Black community once in Montreal. His life speaks of a complexity of language not often explored in narratives of Quebec’s English-speaking community, particularly in those histories about Blacks in the province. I trust this will be the beginning.
Parallel title: QUESCREN Working Paper no.3

The Philanthropist : The Life and Legacy of Jeffery Hale - Donovan, Patrick (Jeffery Hale - Saint Brigids (JHSB), 2020)
In Quebec City, people associate the name Jeffery Hale with a hospital. While Hale certainly helped create the institution that bears his name, his story and legacy go well beyond its walls. Unlike most English-speaking immigrants who came to Canada, Jeffery Hale’s ancestors were rich, powerful, and very well connected. They lived a privileged life with strong transatlantic ties to the Royal Family and the colonial military. They furthered a British imperialist agenda and made decisions that shaped the destiny of North America.

Celebrating 40 Years - Literacy Quebec (LQ) (2020)
The year was 1980 and the world was undergoing massive change. CNN launched, the Rubik’s cube went on sale and the Iran-Iraq war began. Closer to home, Quebecers voted in a sovereignty referendum to remain part of Canada, while the sports scene saw the Montreal Canadiens fail in their quest for a fifth consecutive Stanley Cup. But something else historic was also brewing in the province that year: Laubach Literacy Canada-Quebec (LLC-Q), the forerunner of Literacy Volunteers of Quebec, now known as Literacy Quebec.

Society Pages - Morrin Centre (2020)
Number of pages: 28

Society Pages - Morrin Centre (2020)
Number of pages: 32

Society Pages - Morrin Centre (2020)
Number of pages: 24

Society Pages - Morrin Centre (2020)
Number of pages: 32

Quebec Past and Present : 7th Colloquium on Quebec Studies - Eastern Townships Resource Centre (ETRC); Bishop's University; State University of New York Plattsburgh (2019)
issued: March 29, 2019/March 30, 2019

Semaji - Black Community Resource Centre (BCRC) (2019)
Number of pages: 11

Agriculture : Dear Diary,... : Documentary Record for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Agriculture : Dear Diary,... : Student's Workbook for Elementary School - Eastern Townships Resource Centre (ETRC) (2019)

Agriculture : Dear Diary,... : Student's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Agriculture : Dear Diary,... : Teacher's Workbook for Elementary School - Eastern Townships Resource Centre (ETRC) (2019)

Eastern Townships Archives Portal User Manual - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : Development of the Eastern Townships by the Loyalists : Documentary Record for Elementary School - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Development of the Eastern Townships by the Loyalists : Teacher's Workbook - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Development of the Eastern Townships by the Loyalists : Teacher's Workbook for Elementary School - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Development of the Eastern Townships by the Loyalists : Teacher's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Settlement of the Eastern Townships by the Loyalists : Myth or Reality? : Documentary Record for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Settlement of the Eastern Townships by the Loyalists : Myth or Reality? : Student's Workbook - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Settlement of the Eastern Townships by the Loyalists : Myth or Reality? : Student's Workbook for Elementary School - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Settlement of the Eastern Townships by the Loyalists : Myth or Reality? : Student's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Documentary Record for Elementary School - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Documentary Record for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Student's Workbook for Elementary - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Student's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Teacher's Workbook for elementary school - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Teacher's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

The Verdun Stories - Evangelista, Anna; Purcell, Gary; Thomas, Gabrielle (2019)

Message For Our Veterans - Maurice, Cornella (2019)

Society Pages - Morrin Centre (2019)
Number of pages: 28

Society Pages - Morrin Centre (2019)
Number of pages: 24

Society Pages - Morrin Centre (2019)
Number of pages: 24

Society Pages - Morrin Centre (2019)
Number of pages: 20

Home and Schools 1945-2019 - Quebec Federation of Home and School Associations (QFHSA) (2019)

Vital Communities and Critical Institutions for the Transmission of English-speaking Quebec’s Cultural, Social, and Historical Identity - Townshippers' Association (2019)
This paper will demonstrate how the role of education in a minority language context is much more comprehensive than simply ensuring academic success or instruction in English and is inherently linked to the transmission of its collective history and culture over generations with particular emphasis on the English-speaking community of Quebec (hereafter referred to as the ESCQ), who are struggling to sustain their vitality.
Keywords: Official Language Minority Community (OLMC)

Quebecers Attachment to Canada: One year after the 150th - Jedwab, Jack; Warren, Jean-Philippe (2018)

Attachment to Quebec and Recent Historic Markers - Jedwab, Jack; Warren, Jean-Philippe (2018)

Message For Our Veterans - Maurice, Cornella (2018)

Society Pages - Morrin Centre (2018)
Number of pages: 20

Society Pages - Morrin Centre (2018)
Number of pages: 24

Society Pages - Morrin Centre (2018)
Number of pages: 24

Society Pages - Morrin Centre (2018)
Number of pages: 32

Network News - Quebec Community Groups Network (QCGN) (2017)
Number of pages: 14

Resolution 2017-04 : Quebec Secondary III and IV History Curriculum: In Need of Change - Quebec Federation of Home and School Associations (QFHSA) (2017)

Society Pages - Morrin Centre (2017)
Number of pages: 16

Society Pages - Morrin Centre (2017)
Number of pages: 16

Society Pages - Morrin Centre (2017)
Number of pages: 16

Society Pages - Morrin Centre (2017)
Number of pages: 16

Short History of Official Language Advocacy : English-Language Television in Quebec - English Language Arts Network (ELAN) (2016)
Keywords: Official Language Minority Community (OLMC)

Portrait of the English-speaking Community of Richmond - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2016)
This portrait has been completed by Townshippers’ Association and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre de santé et des services sociaux Val-Saint-François and the Richmond & Region Community Learning Center. Townshippers’ Association is a non-profit, non-partisan community organization focused on promoting and supporting the interests of the English-speaking minority community in the Eastern Townships region of Quebec. The Association was founded in 1979 to ensure the English-speaking community would remain visible despite a declining population. Through a variety of initiatives, Townshippers’ works to strengthen the community and culture of English-speaking Townshippers, open doors of opportunity for youth and promote access to health, social and other services in English. Townshippers’ also strives to encourage the active participation of English-speakers in all aspects of the greater community, in order to help the English-speaking community of the Eastern Townships build bridges with their French-speaking neighbours. The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of Richmond and the surrounding area, in order to inform future actions.
Keywords: Official Language Minority Community (OLMC)

Entre Hong Kong et Québec : Exposition 25 mars 2016-1 janvier 2017 / Hong Kong and the Home Front : Exhibit March, 25 2016-January 1, 2017 - Morrin Centre (2016)

Hong Kong and the Home Front - Morrin Centre (2016)

Society Pages - Morrin Centre (2016)
Number of pages: 24

Society Pages - Morrin Centre (2016)
Number of pages: 16

Society Pages - Morrin Centre (2016)
Number of pages: 20

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Estrie – CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

2011 National Household Survey - Shahar, Charles (The Jewish Community of Montreal, 2015)
This report examines the demographic characteristics of the Holocaust Survivor population in the Montreal metropolitan area based on figures from the 2011 National Household Survey (NHS). The findings compare the characteristics of Holocaust Survivors with Jewish seniors who are not Survivors, and the total population of elderly living in the Montreal CMA. The report also identifies those Survivors who are most vulnerable (physically, economically, socially) and in need of community interventions. As the Survivor population ages and its needs increase, it is imperative to understand the unique circumstances and challenges this population faces.

Resolution 2015-02: History of Residential Schools - Quebec Federation of Home and School Associations (QFHSA) (2015)

Résolution 2015-02 : L'histoire des Pensionnats - Quebec Federation of Home and School Associations (QFHSA) (2015)

Culture, Creativity, Confluence and Collision - Rodgers, Guy (2015)

Message For Our Veterans - Maurice, Cornella (2015)

Society Pages - Morrin Centre (2015)
Number of pages: 16

Society Pages - Morrin Centre (2015)
Number of pages: 16

Society Pages - Morrin Centre (2015)
Number of pages: 12

Society Pages - Morrin Centre (2015)
Number of pages: 12

Quebec and Us : A Mutation of Identity - Rodgers, Guy (Diversité Artistique Montréal (DAM), 2015)

Story of the Coasters Association : Celebrating 25 Years May 1988 - May 2013 - Coasters Association (2014)
The Coasters Association is a non-profit organization formed in St. Augustine in 1988 by a group of concerned citizens of the Lower North Shore. (refer to Annex 1 - Steering Committee) The association was incorporated in La Tabatiere in 1991. It is administered by an elected, volunteer, Board of Directors, with representatives from 5 municipalities and four designated seats (youth, seniors, disabled and education). (refer to Annex 2 – Board of Directors) The Association’s work is mainly funded by the Ministry of Canadian Heritage, while the remainder of its funding is received from other government departments (i.e.: federal, provincial, municipal, and local), as well as fundraising, donations and membership drives. The Coasters Association’s membership stands at 3,542 and with each new member, the Association becomes stronger!
issued: March 21, 2014/March 22, 2014

Building Communities Together : Laurentians, Outaouais, Quebec Region - Seniors Action Quebec (SAQ) (2014)

Literary and Historical Society of Quebec - Morrin Centre (2014)

Society Pages - Morrin Centre (2014)
Number of pages: 20

Society Pages - Morrin Centre (2014)
Number of pages: 16

Society Pages - Morrin Centre (2014)
issued: Autumn, 2014/Winter, 2014 Number of pages: 16

Community Portrait : Sutton - Richardson, Mary; Jobson, Shirley (Community Health and Social Services Network (CHSSN), 2013)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for offi cial language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.
Keywords: Official Language Minority Community (OLMC)

Economic Development Finding Aid - Eastern Townships Resource Centre (ETRC) (2013)

Education Finding Aid - Eastern Townships Resource Centre (ETRC) (2013)

Performing Arts Finding Aid - Eastern Townships Resource Centre (ETRC) (2013)

Settlement & Colonization Finding Aid - Eastern Townships Resource Centre (ETRC) (2013)

Society Pages - Morrin Centre (2013)
Number of pages: 20

Society Pages - Morrin Centre (2013)
Number of pages: 16

Society Pages - Morrin Centre (2013)
Number of pages: 16

Society Pages - Morrin Centre (2013)
Number of pages: 16

Community Portrait of Bonne-Espérance - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2012)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.
Keywords: Official Language Minority Community (OLMC)

Community Portrait : New Carlisle - Richardson, Mary; Gauvin-Racine, Joëlle (Community Health and Social Services Network (CHSSN), 2012)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.
Keywords: Official Language Minority Community (OLMC)

Saint Brigid's and its Foundation : A Tradition of Caring Since 1856 - Donovan, Patrick (Jeffery Hale - Saint Brigids (JHSB), 2012)
Excursions have always been part of Saint Brigid’s history. In the summer of 1894, the orphans piled into horse-drawn trams and wagons headed for the rural hinterland of Sainte Foy, where they enjoyed a picnic on Mr. Boyce’s farm. While horse-drawn trams are a thing of the past, and Sainte Foy now has more parking lots than farms, the home’s residents still enjoy trips to see the fall colours, go fishing, or enjoy a spot of shopping. In the following pages, the SAINT BRIGID’S HOME FOUNDATION invites you on a different sort of journey: a trip through time that takes you from the beginnings of the home to the present day.

Society Pages - Morrin Centre (2012)
Number of pages: 16

Society Pages - Morrin Centre (2012)
Number of pages: 20

Society Pages - Morrin Centre (2012)
Number of pages: 16

Society Pages - Morrin Centre (2012)
issued: Winter, 2012/Winter, 2013 Number of pages: 9

Society Pages - Morrin Centre (2011)
Number of pages: 20

Society Pages - Morrin Centre (2011)
Number of pages: 16

Society Pages - Morrin Centre (2011)
issued: Summer 2011/Fall, 2011 Number of pages: 24

Society Pages - Morrin Centre (2010)
Number of pages: 16

Society Pages - Morrin Centre (2010)
Number of pages: 16

Society Pages - Morrin Centre (2010)
Number of pages: 16

Society Pages - Morrin Centre (2010)
Number of pages: 8

Community, Commitment, Cooperation, Celebrating our Past, Building our Future / Communauté. Engagement. Collaboration. Célébrer le passé. Bâtir le futur - Quebec Community Groups Network (QCGN) (2010)
Parallel title: 1994-1995 - 2009-2010
Keywords: Official Language Minority Community (OLMC)

Assessing the English-speaking Community's Capacity to Access Arts, Culture, and Heritage in Nine Regions of Quebec : A Report on Phase One of the "Enhancing Access to Cultural Expression" Project (EACE) - Quebec Community Groups Network (QCGN); Palmer, Lise (2010)
In 2008, the Quebec Community Groups Network (QCGN) Board of Directors passed a formal resolution to prioritize the development of the Arts, Culture and Heritage sector. This area was prioritized by a majority of members in the Network and was supported by the Board. An Arts, Culture and Heritage working group was created to develop a policy framework in this area to streamline and guide the activities of the Network. The main partners in this endeavour were the English Language Arts Network (ELAN) represented by Guy Rodgers, the Quebec Anglophone Heritage Network (QAHN) represented by Kevin O'Donnell and Dwane Wilkin and the QCGN represented by Sylvia Martin-Laforge. Jane Needles also participated in the working group representing both the QCGN and ELAN. The policy framework, which was completed in November 2008, identified key areas of intervention over the next five years to support the dynamic growth and development of the cultural expression of English-speaking Quebec. The first was a project to access cultural expression through expanded partnerships. This current project “Enhancing Access to Cultural Expression” is a direct result of the prioritization of access to cultural expression. The other areas of priority included recognition and support through visibility - which is currently being addressed through the RAEV project being implemented by ELAN - and the creative economy - an issue yet to be addressed.

Semaji - Black Community Resource Centre (BCRC) (2009)
Number of pages: 20

Entry Island Tragedies - Feltmate, Thelma (2009)

Ladies' Protestant Home 1859-2009 : 150 Years of History - Donovan, Patrick; Hayes, Ashli (2009)
This is the story of how, for the past 150 years, English-speakers in Quebec saw needs in the community and reached out to meet them. The Ladies’ Protestant Home was founded in 1859, a time when epidemics, poor work conditions, and frequent urban fires made life difficult for the poor. There was a crying need for institutions to help out. In its early years, the Home provided temporary shelter for poor and destitute Protestant immigrant women. Its mandate evolved over the years, with an increasing focus on serving the elderly from the 1950’s onward. The Home eventually reached out to non-Protestants, Francophones, and men before closing down in 1990. For the past two decades, the Quebec Ladies’ Home Foundation has continued to manage assets from the Home's sale towards the purpose of providing health and social services to English-speakers in Quebec City.

Society Pages - Morrin Centre (2009)
Number of pages: 12

Society Pages - Morrin Centre (2009)
Number of pages: 16

Society Pages - Morrin Centre (2009)
Number of pages: 8

Lower North Shore Heritage Workbook : Following in the Footsteps of the Explorers - Anderson, Monica; Benoit, Kristina; Blattel, Adrienne; Cochrance, Candace (Coasters Association, 2008)
History is the study of past human events and activities. Studying history can help us better understand where we come from and therefore who we are as people. Historians have a lot in common with explorers, only they are traveling through time AND place. They hunt for clues about how people lived and acted in the past. To do this, they must use a lot of tools such as books, original documents, drawings and maps, and artefacts. They talk to people who might have lived through the time they are studying or who know stories handed down from that time. Some, like the movie character Indiana Jones, take a pick and shovel to dig in the earth to find answers to their question about the past. After they have found as much information as possible, they piece their story together and present it in books, museum exhibits, or documentaries. Being an historian takes patience and hard work but, like exploring, it can also be exciting to find out new things about olden times.

Entry Island School Yearbook - Entry Island School (2008)
issued: 2008/2009

Ancestors : Life, Death, and Descendants of Quebec City's Anglophones - Morrin Centre (2008)
Quebec City’s cemeteries have lots to say about our ancestors and the past. They are places of remembrance for those close to the departed, but they are also a storehouse of memories for the whole community. Cemeteries are closely linked to religious belief : They express a particular vision of the world, a set of values and a culture.

Building the City : The Influence of English Speakers on Quebec City's Architecture - Morrin Centre (2008)
Quebec City is praised for its quintessential Frenchness, yet a closer look at its architecture reveals a city with a strong British influence. Ninety-five per cent of the city was built or modified after the British conquest in 1759. In the middle of the ninete nth century, half the people in the Upper Town were English speakers, and they left a clear mark on the built environment. Many of the city’s important landmarks, from the Château Frontenac to the Price Building, were designed by English-speaking architects.

People and Faith : The Religious Life of English Speakers in Quebec City - Morrin Centre (2008)
Through this tour, you’ll learn about Quebec City’s anglophones through their places of religious worship and practice. We’ll look at distinctions between different forms of belief and you’ll gain a better understanding of Quebec’s religious landscape.

People of the River : Anglophone Life on the St. Lawrence - Morrin Centre (2008)
The Greek historian Herodotus summed up Egypt’s dependence on its great river by calling the country a “gift of the Nile.” In the same way, it could be said that Quebec is a gift of the St. Lawrence. The St. Lawrence was the “boulevard” of the territory’s first inhabitants, the Aboriginal people. Then it became the access route for French explorers. Samuel de Champlain thought it was a route to China, and this was a determining factor in his decision to found a colony at Quebec.

Rediscover Quebec City's Anglo Heritage Through Four Self-Guided Tours / Redécouvrez le visage anglophone de Québec à l'aide de quatre visites autoguidées - Morrin Centre (2008)

Society Pages - Morrin Centre (2008)
Number of pages: 12

Society Pages - Morrin Centre (2008)
Number of pages: 12

Society Pages - Morrin Centre (2008)
Number of pages: 12

Society Pages - Morrin Centre (2008)
Number of pages: 12

Quebec City's Literary Heritage : A Bibliography - Donovan, Patrick (Literary & Historical Society of Quebebc, 2007)
The Literary and Historical Society of Quebec (LHSQ), founded in 1824, has a mandate to foster English-language culture in the Quebec City region and to share its diverse heritage. Literature is a vital element in this heritage, and the LHSQ has taken on a project to celebrate Quebec City’s English-language literary heritage. The first step of this project is to generate an accessible knowledge base, or bibliography. This tool will have several repercussions: book purchases for the LHSQ’s library, written articles to promote these books, and the hosting of literary events in 2007 and 2008. This project is financed by the Department of Canadian Heritage as part of the Development of Official-Language Communities Program - Community Life component.

History of the Coasters Association 1988-2007 - Maurice, Cornella (Coasters Association, 2007)

Society Pages - Morrin Centre (2007)
Number of pages: 20

Society Pages - Morrin Centre (2007)
Number of pages: 12

Society Pages - Morrin Centre (2007)
Number of pages: 16

Society Pages - Morrin Centre (2007)
Number of pages: 12

Historical Heritage of English Communities On the Magdalen Islands - Currie, Wynn (2006)

Society Pages - Morrin Centre (2006)
Number of pages: 8

Society Pages - Morrin Centre (2006)
Number of pages: 16

Society Pages - Morrin Centre (2006)
Number of pages: 12

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)
Number of pages: 7

Brion Islands - Council for Anglophone Magdalen Islanders (CAMI) (2005)

Entry Island Museum Family Names and Their History - Entry Island Historical Museum (2005)

Naming the Laurentians : A History of Place Names 'Up North' - Graham, Joseph (Les Editions Main Street Inc., 2005)

Society Pages - Morrin Centre (2005)
Number of pages: 8

Society Pages - Morrin Centre (2005)
Number of pages: 8

Society Pages - Morrin Centre (2005)
Number of pages: 8

Society Pages - Morrin Centre (2005)
Number of pages: 8

They Are All Our Heroes : Lest We Forget - Morrison, Edna (2005)

Entry Island School Yearbook - Entry Island School (2004)
issued: 2004/2005

Society Pages - Morrin Centre (2004)
Number of pages: 13

Society Pages - Morrin Centre (2004)
Number of pages: 12

Society Pages - Morrin Centre (2004)
Number of pages: 12

Society Pages - Morrin Centre (2004)
Number of pages: 8

Remembering our Heritage and Culture - Fequet Griffin, Priscilla (Coasters Association, 2003)
The project started on June 16, 2003, at which time a schedule of activities was produced (see annex 1). Following this, a list of all seniors (65 and up), within the Municipality of Bonne Esperance, was developed containing their ages and phone numbers (see annex 2). All seniors were contacted for their participation in this project, in which all ninety-nine were willing to take part.

The Schools of Entry Island - Entry Island Historical Museum (2003)

Transcript of Interview with Jack McLean (2003)

Historical Heritage Sites of the Magdalen Islands' Anglophone Communities / Les sites patrimoniaux historiques des communautés anglophones des Îles-de-la-Madeleine - Clarke, Norma Jean (2003)

Entry Island School Yearbook - Entry Island School (2002)
issued: 2002/2003

Society Pages - Morrin Centre (2002)
Number of pages: 6

Society Pages - Morrin Centre (2002)
Number of pages: 7

Alliance Quebec News Magazine - Alliance Quebec (AQ) (2001)
Number of pages: 38

Entry Island Life & Times - Entry Island Historical Museum (2001)

Entry Island School Yearbook - Entry Island School (2001)
issued: 2001/2002

Casseroles For All Occasions - Welsh, Ada (2001)

Entry Island Transportation & Post Offices & Hydro Quebec - Entry Island Historical Museum (Entry Island, QC, 2000)

History of Island Houses - Entry Island Historical Museum (2000)

Nurses of Entry Island - Entry Island Historical Museum (2000)

Grosse-Ile High School - Grosse-Ile High School (2000)
issued: 2000/2001

Island Tragedies at Sea - McCartney, Katherine; Pealey, Rodrick; Dickson, Jennifer; Goodwin, Robina (Council for Magdalen Islanders (CAMI), 2000)

How to Celebrate "La Fête Nationale" - Johnson, William (1999)

Entry Island's 1999 CookBook & Short Stories - McLean, Ellen (1999)

Deaths at Brion Island - Clark, Spencer (1998)

CAMI's Memories of Yesteryear - Council for Anglophone Magdalen Islanders (CAMI) (1997)

Old Medicinal Remedies from Our Ancestors - Clarke, Norma Jean (Williams & Crue (1982) Ltd., 1997)

Happy Anniversary C.A.M.I. : March 1987-1997 (1997)
Number of pages: 16

Island Schools - Goodwin, Amanda (1997)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1995)
Number of pages: 16

A Dynamic Environment on the Magdalen Islands - Clark, Rachelle (1995)

Lighthouses on the Magdalen Islands - Clark, Rachelle (1995)

The Jewels of the Gulf : Our Beautiful Magdalen Islands (Williams & Crue (1982) Ltd., 1993)

Centre Hospitalier Jeffery Hale's Hospital Centre 1865-1990 - Gelly, Alain (1990)

City Trek '90 - O'Gallagher, Marianna (1990)

The Magdalen Islands (1988)
issued: June, 1988/August, 1988 Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1986)
Number of pages: 16

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1986)
Number of pages: 16

A Study of Brion Island : Magdalen Islands, Quebec - The Information to Magdalen Island Anglophones Project (1985)

Help us complete the picture! The Alliance Local History Resource Guide - Alliance Quebec (AQ) (1984)

Sharing Recipes : A Book of [Favourite] Recipes - Grosse Isle Branch of the Quebec Women's Institute (Circulation Service, 1984)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1979)
Number of pages: 17

Submission to the Task Force on Canadian Unity by Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1978)
For the third time in four years the Quebec Federation of Home and School Associations, a non-political association, finds, that because of its concern for the heritage and welfare of all children in Quebec, it must take a public position on a matter not directly educational.

May News 1977 Entry Island School - Entry Island School (1977)

Unknown, New Venture - Powell Vallis, Effie Rebecca (1977)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1967)
Number of pages: 8

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1967)
Number of pages: 8

81st Annual Report of Jeffery Hale's Hospital and the Training School for Nurses : with a List of the Governors, Officers, and Subscribers for 1946 - Jeffery Hale's Hospital (Jeffery Hale - Saint Brigids (JHSB), 1946)

A Generation of Seafarers

Bird Rock

Bird Rock / Rocher aux oiseaux

Entry Island

Lighthouse Keepers and Legends of the Great Bird Rocks / Les gardiens de phare et légendes du rocher aux oiseaux

Magdalen Island Facts

Maritime Transport

Place Names : Entry Island

Points of Interest : Plaques on Entry Island

Short Stories...

The Beautiful Isles of Magdalene

The English Community of Montreal

The Home of Simeon Clarke : Site of the First Telegraph Office at Grosse Isle

Black Community Archive of Montreal - Bayne, Clarence S
The human social system is a complex adaptive system. It consists of a network of live and non-live agents interacting and responding to continuous change in the agents and system itself: a change I any agent causes other agents to change. This causes the system to change, which causes further changes in agents, and the process continues infinitely.

Qui suis-je? / Who am I? - Centre for Access to Services in English (CASE)

Qui suis-je? / Who am I? - Centre for Access to Services in English (CASE)

Conserving History Through Generations : Vignettes of the Valley - Chateauguay Valley Regional High School

Island Stories - Chenell, Brenda

Self-Guided Tour of the English-speaking Community of the Magdalen Islands - Chenell, Melissa

Down the Lane to Wallie's : A Story About Life on the Magdalen Islands - Clarke-Selander, Dorothy

Citadel Foundation - Donovan, Patrick

Historical Museum of Entry Island - Entry Island Historical Museum

Multimedia Theatre Presentation : The Philanthropist - Jeffery Hale - Saint Brigid's (JHSB)

Prisoners, Students and Thinkers / Prisonniers, élèves et penseurs - Morrin Centre

QCGN Statement Regarding the French Language - Quebec Community Groups Network (QCGN)
Keywords: Official Language Minority Community (OLMC)

Portrait of the English-speaking Population of the South Shore : Montérégie-Centre - Richardson, Mary (Community Health and Social Services Network)
This community portrait is a project of the Assistance and Referral Centre (ARC) and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre intégré de santé et de services sociaux de la Montérégie-Centre. ARC is a community-based organization that promotes access to services in English through networking; information and referrals; and supporting the development of community-wide initiatives. The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of Montérégie-Centre, in order to inform future actions. To do so, we present a brief introduction into community development and its connections to health and well-being. Then we provide an overview of the South Shore region (Montérégie-Centre), including some history of the English-speaking community. This is followed by some key statistics on the English-speaking population, using the health territory divisions. Finally we present some complementary information on healthy habits among youth and adults.

Conserving History Through Generations : Building Bridges Over Time - St-Willibrord Elementary School

Jewels of the Gulf : the Isles of Madgalen - The First Informer